2008
DOI: 10.1091/mbc.e07-09-0954
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-Box RNA Helicase Ded1p Affects and Accumulates inSaccharomyces cerevisiaeP-Bodies

Abstract: Recent results suggest that cytoplasmic mRNAs can form translationally repressed messenger ribonucleoprotein particles (mRNPs) capable of decapping and degradation, or accumulation into cytoplasmic processing bodies (P-bodies), which can function as sites of mRNA storage. The proteins that function in transitions between the translationally repressed mRNPs that accumulate in P-bodies and mRNPs engaged in translation are largely unknown. Herein, we demonstrate that the yeast translation initiation factor Ded1p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
104
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 55 publications
11
104
0
4
Order By: Relevance
“…RCK/p54 family members have an interesting mechanism of transcriptional regulation in that they act to recruit mRNA transcripts to cytoplasmic P-bodies for degradation via a CCR4-dependent mechanism of decapping and deadenylation followed by 3Ј-5Ј degradation (21). In the present study, RNA immunoprecipitation of an epitope-tagged Vad1 followed by microarray identified MF␣ transcripts as direct targets within a set of C. neoformans genes.…”
mentioning
confidence: 57%
“…RCK/p54 family members have an interesting mechanism of transcriptional regulation in that they act to recruit mRNA transcripts to cytoplasmic P-bodies for degradation via a CCR4-dependent mechanism of decapping and deadenylation followed by 3Ј-5Ј degradation (21). In the present study, RNA immunoprecipitation of an epitope-tagged Vad1 followed by microarray identified MF␣ transcripts as direct targets within a set of C. neoformans genes.…”
mentioning
confidence: 57%
“…This observation may be explained by redundant processing helicases in the Figure 2.-Orb2, poly-A binding protein (PABP), Rm62/Dmp68, and Sm proteins are present on dFMR1-containing foci in neurites of cultured Drosophila primary neurons. Neurites of dissociated and cultured larval neurons contain distinct FMR1-containing mRNPs that also contain several molecules involved in translational control (Barbee et al 2006;Beckham et al 2008;Kwak et al 2008). These particles visualized in processes of motor neuron expressing dFMR1-YFP (from C380Gal4; ChaGal80; UASdfmr1-YFP larvae) also contain Orb2 (A-C), PABP (D-F), Rm62 (G-I), and Sm ( J-L) proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The former is thought to be involved in translation (68 -71) and in mRNA storage in cytoplasmic processing bodies (P-bodies) (72). The latter was isolated as a differentially expressed cDNA, noticeably more abundant in artificially aged but viable seeds (73), relative to un-aged seeds just after the completion of germination of both groups (axis ϳ0.5 cm long).…”
Section: Discussionmentioning
confidence: 99%